The role of industrial placement in vocational training of engineers-teachers of the transport industry - Ivanova, A. (Problems of Engineer-Pedagogical Education, 2019)
The article considers the essence and features of industrial placement as an independent form of industrial training, in the process of which students perform real production activities specified in the academic curriculum, and reveals objective and subjective reasons conditioned by the problems that have emerged during the last decades in the country’s production system. The paper characterizes the prospects of organizing industrial placement taking into account the provisions of the public policy on vocational training. On the basis of the analysis of certain principal provisions for industrial placement that scientists pay special attention to, the author defines the main functions of future specialists’ vocational training, which are realized exceptionally during industrial placement: real-life socialization of young people; development of a positive attitude towards the future professional activity on the basis of real-life conditions, inclinations, interests, aspirations, and personality qualities; expansion of the content of future specialists’ educational and vocational training; development of independence and a strong need for permanent self-perfection. The author has come to the conclusion about the necessity of paying attention to the purposeful pattern of using industrial placement for the development of vocational competence of future engineers-teachers taking into account educational and pedagogic potential of industrial placement during the process of vocational training. The aim of industrial placement of future engineers-teachers of the transport industry is defined regarding their professional functions. The paper outlines some prospects of designing a system of the development of vocational competences of future specialists, using the potential of industrial placement.